The psychology of Gaelic games: a co-produced scoping review to inform research, policy, and practice - Jackman, P. C.; Lane, A.; Wells, N.; Kirby, K.; Bird, M. D. (International Journal of Sport and Exercise Psychology, 2024)
Gaelic games are a family of indigenous Irish sports played in Ireland and across the world. With recent growth in research on the psychology of Gaelic games and developments in sport science policy in this context, there is a need to map and clarify understanding of psychology in Gaelic games. Against this backdrop, we conducted a scoping review that aimed to identify and synthesise current literature on the psychology of Gaelic games, with the intention of generating findings that could have implications for research, policy, and practice. After electronic database searches and manual searches up to September 2023, we included data from 42 articles involving 4963 Gaelic games participants in the review. We organised findings into eight categories: mental health and wellbeing; burnout; youth coaching practices; psychology of injury; attentional processes; optimal experiences and performing under pressure; identity; and female coach development. In light of the findings, we offer (a) five recommendations for researchers to strengthen the quality of research in future, and (b) five implications for policy and practice, some of which might also be transferable to other sport contexts. We believe that consideration of our recommendations for research can build a stronger and more coherent evidence base for policy and practice. By doing so, this can ultimately lead to more meaningful and tangible benefits for all in Gaelic games.